PF.55 Intrauterine Transfusion For Parvovirus B19 Infection Over Last Decade. (26th April 2013) - Wu, P; Cameron, AD; Gibson, JL; Brennand, J; Ledingham, MA
Abstract : Intrauterine transfusion (IUT) cases for Parvovirus B19 infection over 2002–2011 were reviewed. Our unit receives referrals from Scotland and Northern Ireland. Most were referred in 2008 ( n = 5) and 2009 ( n = 7). In other years there were <3 cases. Thirty patients underwent 48 IUTs (mean 1.6, range 1–3). Twenty-six fetuses had middle cerebral artery Doppler peak systolic velocity values documented. All were >1.5 multiples of median prior to first IUT. At initial assessment, 25 fetuses were hydropic and 4 had ascites. Pre-IUT haematocrit value was available in 27 pregnancies: <10% in 15 and 10–19% in 5 cases, in keeping with fetal anaemia. Initial IUT was most frequently performed between 21–24 ( n = 13) followed by 17–20 weeks gestation ( n = 9) (range 17–32 weeks). Intrauterine or neonatal death occurred in 9 hydropic fetuses that had bradycardia, thrombocytopenia, difficult procedure or severe anaemia. No reasons were identified in 2 cases. However, these did not have pre-transfusion haematocrit values. Seven procedures had other complications e.g. cord haematoma, technically difficult, bradycardia and spontaneous rupture of membranes. This pregnancy was conservatively managed with a live birth at 36 weeks gestation. Live births occurred in 14 pregnancies. Seven women were lost to follow-up. Improved capture of outcome data is required. Short term outcomes were available in 8 neonates: 6 required no treatment, 1 had phototherapy and 1 had a neonatal death. We conclude that poor outcomes following IUT can be predicted at the time of procedure and that IUT can rescue a fetus destined for intrauterine loss to a healthy outcome.